Contextualizing agile software development. Issue 4 (27th September 2011) - Kruchten, Philippe; Biró, Miklós; Messnarz, Richard; Palacios, Ricardo Colomo
SUMMARY This paper presents a contextual model for software‐intensive systems development to guide the adoption and adaptation of agile software development practices. This model was found especially useful when the project context departs significantly from the "agile sweet spot", that is, the ideal conditions in which agile software development practices originated from, and where they are most likely to succeed, "out of the box". This is the case for large systems, distributed development environment, safety‐critical systems, system requiring a novel architecture, or systems with an unorthodox business model or governance model. Copyright © 2011 John Wiley & Sons, Ltd.